Equal Pay for Better Health: The Health Cost of the Gender Wage Gap - Susan L. Averett; Adam Biener; Olena Ogrokhina (Institute of Labor Economics (IZA), 2024)
This paper explores the relationship between gender wage gaps and women's overall health. Using data from the 2011-2019 Current Population Survey, we employ entropy balancing to create comparable samples of men and women and estimate wage gaps for full-time employed working-age women. Adjusting for individual, occupation, and industry characteristics, we estimate the association between wage gaps and self-rated health. Our results suggest that closing the wage gap results in a 1.2 percent reduction in women reporting poor or fair health, equivalent to nearly 170,000 fewer women. These effects are more pronounced for women with below-median wages or in male-dominated jobs.
Keywords: F02; F34; F41; G15; 330; wage gap; health; women